Efektivitas Model Pembelajaran Learning Starts with A Question (LSQ) Terhadap Hasil Belajar Matematika Siswa - Syaibah, Siti; Anwar, Azwar; Widyawati, Eka (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research aimed to determine the effectiveness of the learning model of learning starts with a question (LSQ) on students’ mathematics learning outcomes. The type of research is true ekxperimental with a quantitative approach. In this study, the design used was a post-test-only control group design, namely placing research subject into two classes which were divided into experimental class and control class, with sampling used a simple random sampling technique, which means that the sample was taken randomly from the population. The instruments used in this research were lesson plans, student worksheets, and test sheets. Then, the technique of collecting data used written test on the type of essay tests. The last data was documentation to obtain school data information. The data analysis techniques used are the swimmer test (normality test, homogeneity test) and hypothesis testing (t test and z test). The result of this research showed that the average score for students’ mathematics learning outcomes applied with the learning starts with a question (LSQ) learning model = 93,37, for classes applied with the conventional learning model = 72,00. Based on the result of the different tests (final test) using the z- test, the value z-count > z-tabel was obtained (12.00733 > 1.6450). So, it can be concluded that the learning starts with a question (LSQ) learning model is effective on the students’ mathematics learning outcomes